Solusi Penggunaan Media Pembelajaran Bahasa Indonesia di Sekolah Dasar - Atika Maulidina Hs (STKIP AL HIKMAH SURABAYA, 2024)
The aim of this research is to determine the urgency of HOTS in elementary school science learning, the problems in its implementation, and solutions to these problems, so that the goals of HOTS in the 21st century can be achieved. The method used is a literature study of 15 related articles to obtain information related to the objectives that have been set. The results obtained show that HOTS is very important to apply to elementary school science learning, but in its implementation there are still problems including students' lack of high-level thinking abilities, inappropriate assessments, and the use of irrelevant teaching materials. Things that can be done to solve the problem are by applying the concept of a scientific approach, changing the assessment system to an authentic assessment system, and improving the quality of teaching materials so that they are in line with HOTS and the learning objectives formulated by K13 to face the 21st century.